La improcedencia de embargar bienes o una parte de ellos cuando el origen de los mismos es la posesión efectiva - Bahamonde Palacios, Diana Carolina (2015)
The center for the preparation of this work consists in arguing conceptual, doctrinal and legally the following fact: that the institution known to the Ecuadorian legislation from the years 10 of the twentieth century as actual possession suffers from a structural defect: Does not constitute a property tleti. And, even more so when there is the declaration of actual possession in judicial way, actual possession does not enter the trade, That is to say, to the economy where the flow of competition and pricing has an impact on the valuation of things, and therefore does not constitute an important element for the assessment of a thing. And as a result, the actual possession is not subject, by legal logic, however by the legal reason for that is not title of property. There have been circumstances in the judges can order however, based on the simple fact that as a share of the property May be ordered this precautionary measure, when in reality the actual possession makes its appearance only by succession of death.